The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s13197-018-3456-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of extraction protocol for Carica papaya L. to obtain phenolic rich phyto-extract with prospective application in chevon emulsion system

Abstract: The present study optimized the extraction protocol conditions to obtain the antioxidant-rich bioactive extracts from Carica papaya L. (Papaya) leaves. A Box and Behnken Design (BBD) consisting of three different extracting variables viz. extracting temperature (60-70°C), time (10-20 min) and solvent concentration (55-65%) was used. Antioxidant efficacy was recorded by evaluating four responses viz. ABTS, DPPH, SASA and total phenolic contents. The optimized model predicted, solvent concentration of 60% with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The b* values of color parameter (denoting the yellowness in product) showed a significant (p # 0.01) difference and the results obtained in buffalo veal and chevon slices were 16.5 and 12.3, respectively. However Devatkal et al (2010) reported Hunter color values (L, a and b) in chevon patties as 39.0, 8.4 and 18.7, respectively, whereas Jagtap et al(2019b) observed the color (L, a and b) values in goat meat nuggets as 50.1, 10.6 and 14.6, respectively.…”
Section: Sensory Characteristics Of Meat Slicesmentioning
confidence: 94%
“…The b* values of color parameter (denoting the yellowness in product) showed a significant (p # 0.01) difference and the results obtained in buffalo veal and chevon slices were 16.5 and 12.3, respectively. However Devatkal et al (2010) reported Hunter color values (L, a and b) in chevon patties as 39.0, 8.4 and 18.7, respectively, whereas Jagtap et al(2019b) observed the color (L, a and b) values in goat meat nuggets as 50.1, 10.6 and 14.6, respectively.…”
Section: Sensory Characteristics Of Meat Slicesmentioning
confidence: 94%
“…For health conscious people, chevon is a good red meat option. Despite chevon being “despised” by indigenous black South Africans who only prefer to consume it at special traditional ceremonies, its products such as sausages, nuggets and kebabs are becoming more popular [ 1 ]. However, meat handling speeds up lipid peroxidation and microbial activity [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Goat meat is highly nutritious as it provides all the necessary nutrients required for growth and development of healthy body (Haenlein, 2004). Goat meat is consumed by all the segments of the society without religious/social taboos, gaining attraction as a good source of red meat in the world (Jagtap et al, 2019). Goat meat nugget is a comminuted meat product, prepared by reducing size of particles in grinder and bowl chopper by incorporating raw meat with additives such as spices, condiments, etc., subjected to steam cooking to form finished product (Gadekar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Meat is highly perishable commodity due to its high moisture and nutrient contents specially protein and fats, which results in faster microbial growth and oxidative quality deterioration (Al-Hijazeen et al, 2016). Prevention of microbial growth and retarding lipid, as well as protein oxidation during storage are the challenges faced by the meat industry/food producers that are essential to upholding the wholesomeness, quality and safety of products of meat origin (Jagtap et al, 2019). Synthetic preservatives were being widely used to curtail the microbial growth and thereby improving storage span of meat foods (Lorenzo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation